Assessment of self-rated health: The relative importance of physiological, mental, and socioeconomic factors - Hamplová, Dana; Klusáček, Jan; Mráček, Tomáš (PloS one, 2022)
BACKGROUND: The general self-rated health (SRH) question is the most common health measure employed in large population surveys. This study contributes to research on the concurrent validity of SRH using representative data with biomarkers from the Czech Republic, a population not previously used to assess the SRH measure. This work determines the relative contribution of biomedical and social characteristics to an individual's SRH assessment. Studies have already explored the associations between SRH and markers of physical health. However, according to a PubMed systematic literature search, the issue of the relative importance of physiological and psychosocial factors that affect individuals' assessments of their SRH has generally been neglected. METHODOLOGY/PRINCIPAL FINDINGS: Using data from a specialized epidemiological survey of the Czech population (N = 1021), this study adopted ordinary least squares regression to analyze the extent to which variance in SRH is explained by biomedical measures, mental health, health behavior, and socioeconomic characteristics. This analysis showed that SRH variance can be largely attributed to biomedical and psychological measures. Socioeconomic characteristics (i.e. marital status, education, economic activity, and household income) contributed to around 5% of the total variance. After controlling for age, sex, location, and socioeconomic status, biomarkers (i.e. C-reactive protein, blood glucose, triglyceride, low-density lipoprotein, and high-density lipoprotein), number of medical conditions, and current medications explained 11% of the total SRH variance. Mental health indicators contributed to an additional 9% of the variance. Body mass index and health behaviors (i.e. smoking and alcohol consumption) explained less than 2% of the variance. CONCLUSIONS/SIGNIFICANCE: The results suggested that SRH was a valid measure of physiological and mental health in the Czech sample, and the observed differences were likely to have reflected inequalities in bodily and mental functions between social groups.
Keywords: průzkumy a dotazníky; Socioeconomic Factors; Surveys and Questionnaires; stupeň vzdělání; zdravotní stav; společenská třída; Social Class; Humans; Health Status; zdravé chování; lidé; Educational Status; Health Behavior; socioekonomické faktory